Malaysian sector-specific: transitioning climate-related disclosures from voluntary to mandatory - Ahmad Nazri, Farah Syafiqa Adlina; Hashim, Ummi Junaidda (Universiti Teknologi MARA, Kedah, 2024)
The aim of this conceptual paper is to explore challenges and opportunities for shifting from voluntary to mandatory climate change corporate disclosures among listed firms in Malaysia which are drawn from the environmentally sensitive sectors representing energy, transport utilities and plantations. This study adds to the discussion by looking at how stakeholder, legitimacy and institutional theories affect these disclosures as well as implied understanding of standardized reporting practices in company transparency and sustainability practices. This study serves as an empirical investigation of the various reading strategies applied and being practiced by companies to adapt themselves in a world surfacing climate impacts, provide insight for businesses and policy-makers alike for an informed decision making.